2016
DOI: 10.5539/jmbr.v6n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical (ºOH) Scavenger Power of Tris (hydroxymethyl) Compared to Phosphate Buffer

Abstract: Tris and phosphate buffer are regularly used in experimental investigations. These buffers might have radical scavenger properties toward different kinds of Reactive Oxygen Species (ROS) produced in solutions during chemical reactions like Fenton reaction and gamma radiolysis. Hydroxyl radicals (ºOH) are the most reactive and oxidizing agents having a great potential in oxidization of macromolecules like DNA and proteins. This in vitro study was aimed to evaluate radio-protective effects of Tris and phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…[ 19 ] Additionally, phosphate buffer is found to act as a radical scavenger, which might explain (together with the aforementioned increased deformation resistance) the lower degree of hydrogel contraction we have observed in our γ ‐irradiation experiments (Figure 2B,C). [ 20 ] The reactivity of the residual alkyne groups suggested that it should be possible to glue [ 21 ] or fuse hydrogel objects using γ ‐irradiation ( Figure A). We designed an experiment in which two hydrogel cubes where placed on top of each other inside a closed glass vial.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Additionally, phosphate buffer is found to act as a radical scavenger, which might explain (together with the aforementioned increased deformation resistance) the lower degree of hydrogel contraction we have observed in our γ ‐irradiation experiments (Figure 2B,C). [ 20 ] The reactivity of the residual alkyne groups suggested that it should be possible to glue [ 21 ] or fuse hydrogel objects using γ ‐irradiation ( Figure A). We designed an experiment in which two hydrogel cubes where placed on top of each other inside a closed glass vial.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the effect of plasma on DNA in aqueous solutions partially helped us to select an appropriate culture medium for the collected semen samples. It has been suggested that complex media could interact with the plasma components (particularly ROS) [ 22 ] or change their properties (such as pH) in response to NTP treatment [ 23 ]. Similarly, data collected from the chemiluminescent assay for ROS quantification should be interpreted with caution due to a variety of factors that may affect the signal obtained, such as the medium composition or its pH [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Additionally, phosphate buffer is found to act as a radical scavenger, which might explain the lower degree of hydrogel contraction we have observed in our g-irradiation experiments (Figure 2B and 2C). 26 The reactivity of the residual alkyne groups suggested that it should be possible to glue 27,28 or fuse hydrogel objects using g-irradiation (Figure 3A). We designed an experiment in which two hydrogel cubes where placed on top of each other inside a closed glass vial.…”
mentioning
confidence: 99%